Изучение воздействия препаратов для витальной пульпотомии в молярах белых крыс (Эндодонтия Today, 2020)
The aim of the research was to examine the effect of «Trioxident», «Pulpotec» and «ViscoStat» on the pulp and periodontal tissue of white molars after the vital pulpotomy. All the rats were divided into three groups. «Trioxident» was used in the first group which consisted of 22 experimental animals, «Pulpotec» was used in the second group which consisted of 17 rats and «ViscoStat» was used in the third group which consisted of 18 experimental animals. After experimentally induced pulpitis and pulpotomy one of the studied drugs was imposed. Histological examination of the material was fulfilled in 2 weeks. The area of the reparative dentin was 296,9 mkm2 in group with «Trioxident», 335,0 mkm2 in group with «Pulpotec» and 355,1 mkm2 in group with «ViscoStat». The morphological signs of inflammation of the root pulp were absent in group with «Trioxident». The morphological signs of inflammation of the root pulp in group with «Pulpotec» and «ViscoStat» were determined in 8.3 % and in 71.4 % respectively. The experimental results confirmed that «Trioxident» provides regenerative effect on the pulp. That allows to recommend it to a wider usage in pediatric dentistry for vital pulpotomy.